Electrifying roller for electrophotographic apparatus

By regularly forming the groove portion and the plane portion on the outer peripheral surface of the shaft body of the charged roller for an electrophotography device, and placing roughness forming particles separately, the problem of degradation of surface roughness uniformity is solved, and uniformity of discharge characteristics and image quality is improved.

CN119547019APending Publication Date: 2025-02-28SUMITOMO RIKO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380053713.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-11
Filing Date
2023-07-04
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

When adding particles for roughness formation in conventional electrophotographic equipment, the uniformity of surface roughness is easily reduced, thereby affecting the uniformity of discharge characteristics.

Method used

A charged roller is designed, and the outer peripheral surface of the shaft body is covered with a regularly formed groove portion and a flat surface portion. The groove width, groove depth and width of the flat surface portion are in a specific range. The particles for roughness forming on the groove portion are respectively arranged and the particles on the flat surface portion are adjusted by the thickness difference of the adhesive polymer to ensure uniformity of discharge characteristics.

Benefits of technology

Through this design, the uniformity of discharge characteristics of the charged roller can be significantly improved, the unevenness and fringe problems in the image can be reduced, and the service life of the equipment can be extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119547019A_ABST
    Figure CN119547019A_ABST
Patent Text Reader

Abstract

Provided is a charging roller for an electrophotographic device having excellent uniformity of discharge characteristics. In the charging roller 10, one or more grooves 22 extending in a direction within + / -46 DEG with respect to the circumferential direction y are regularly formed in the axial direction X on the outer peripheral surface of the elastic body layer 14, the groove width w1 is 4 [mu] m to 30 [mu] m, and the groove depth d is 2 [mu] m to 12 [mu] m. The width (w2) of a planar portion (24), which is a portion other than the groove portion (22), in the outer peripheral surface of the elastic body layer (14) is 4-30 [mu] m, the relationship between the angle (theta) of the direction in which the groove portion (22) extends and the circumferential direction (y) and the ratio (w2 / w1) of the groove width (w1) of the groove portion (22) and the width (w2) of the planar portion (24) is a specific relationship, and the surface layer (16) contains a binder polymer (16a) and roughness-forming particles (18). The roughness-forming particles (18) are disposed on the flat surface section (24) and the groove section (22), respectively.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a charging roller for an electrophotographic device which is suitable for use in an electrophotographic device such as a copying machine, a printer, a facsimile machine, etc. which adopts an electrophotographic method. Background Art

[0002] As a charging roller for an electrophotographic device, there is known a charging roller having an elastic layer having rubber elasticity on the outer peripheral surface of an axial body such as a core rod, and a surface layer on the outer peripheral surface of the elastic layer. In addition, in the charging roller, for example, roughness forming particles are sometimes added to the binder polymer of the surface layer depending on the charging characteristics.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2018 / 025870 Summary of the invention

[0006] Problems to be solved by the invention

[0007] However, since the roughness forming particles added to the surface layer are easily aggregated, the uniformity of the surface roughness is easily reduced in the roughness forming method of adding roughness forming particles. In particular, if two or more roughness forming particles with different particle sizes are used to form surface irregularities, each particle with different particle sizes will aggregate, so the uniformity of the surface roughness is particularly likely to be reduced. If the uniformity of the surface roughness is reduced, there is a risk that the uniformity of the discharge characteristics of the charging roller will be reduced.

[0008] An object of the present invention is to provide a charging roller for an electrophotographic apparatus having excellent uniformity of discharge characteristics.

[0009] Means used to solve problems

[0010] The charging roller for an electrophotographic device according to the present invention comprises a shaft, an elastomer layer formed on the outer peripheral surface of the shaft, and a surface layer formed on the outer peripheral surface of the elastomer layer, wherein one or more grooves extending in a direction within ±46° relative to the circumferential direction are regularly formed on the outer peripheral surface of the elastomer layer in the axial direction, the groove width w1 of the groove is greater than or equal to 4 μm and less than or equal to 30 μm, the groove depth of the groove is greater than or equal to 2 μm and less than or equal to 12 μm, the width w2 of a planar portion of the outer peripheral surface of the elastomer layer, which is a portion other than the groove, is greater than or equal to 4 μm and less than or equal to 30 μm, the relationship between an angle θ of the extending direction of the groove with respect to the circumferential direction and a ratio w2 / w1 of the groove width w1 of the groove and the width w2 of the planar portion is in the following relationship (A) to (C), the surface layer comprises a binder polymer and roughness forming particles, the roughness forming particles are respectively arranged on the planar portion and the groove portion of the elastomer layer,

[0011] (A) -5°≤θ≤+5°, 0.7≤w2 / w1≤1.3

[0012] (B) When -22°≤θ<-5° or +5°<θ≤+22°, 1.0≤w2 / w1≤2.0

[0013] (C) When -46°≤θ<-22° or +22°<θ≤+46°, 1.2≤w2 / w1≤2.6.

[0014] Preferably, the surface roughness Rz of the surface layer in the area on the groove portion is greater than 2μm and less than 16μm, and the surface roughness Rz of the entire surface layer is greater than 5μm and less than 26μm. Preferably, the average particle size of the roughness forming particles is greater than 3μm and less than 30μm. Preferably, the material of the roughness forming particles is any one of polyurethane, polyamide, and acrylic resin. Preferably, the thickness of the binder polymer covering the roughness forming particles on the groove portion is thicker than the thickness of the binder polymer covering the roughness forming particles on the plane portion. Preferably, the difference between the thickness of the binder polymer covering the roughness forming particles on the plane portion and the thickness of the binder polymer covering the roughness forming particles on the groove portion is greater than 4μm and less than 16μm. Preferably, the elastomer layer contains at least one of isoprene rubber, nitrile rubber, and epichlorohydrin rubber. Preferably, the binder polymer of the surface layer is any one of polyurethane and polyamide. Preferably, the roughness forming particles are composed of one type of particles. Preferably, a mesh-like groove portion formed by intersecting groove portions extending in a direction within +46° with respect to the circumferential direction and groove portions extending in a direction within -46° with respect to the circumferential direction is formed on the outer peripheral surface of the elastic layer.

[0015] (1) The charging roller for an electrophotographic device according to the present invention comprises a shaft, an elastomer layer formed on the outer peripheral surface of the shaft, and a surface layer formed on the outer peripheral surface of the elastomer layer, wherein one or more grooves extending in a direction within ±46° relative to the circumferential direction are regularly formed on the outer peripheral surface of the elastomer layer in the axial direction, the groove width w1 of the groove is not less than 4 μm and not more than 30 μm, the groove depth of the groove is not less than 2 μm and not more than 12 μm, the width w2 of a flat portion of the outer peripheral surface of the elastomer layer, which is a portion other than the groove, is not less than 4 μm and not more than 30 μm, the relationship between an angle θ of the extending direction of the groove with respect to the circumferential direction and a ratio w2 / w1 of the groove width w1 of the groove and the width w2 of the flat portion is in the following relationship (A) to (C), and the surface layer contains a binder polymer and roughness forming particles, and the roughness forming particles are respectively arranged on the flat portion and the groove portion of the elastomer layer,

[0016] (A) -5°≤θ≤+5°, 0.7≤w2 / w1≤1.3

[0017] (B) When -22°≤θ<-5° or +5°<θ≤+22°, 1.0≤w2 / w1≤2.0

[0018] (C) When -46°≤θ<-22° or +22°<θ≤+46°, 1.2≤w2 / w1≤2.6.

[0019] (2) Preferably, in the above (1), the surface roughness Rz of the surface layer in the region above the groove portion is 2 μm or more and 16 μm or less, and the surface roughness Rz of the entire surface layer is 5 μm or more and 26 μm or less.

[0020] (3) Preferably, in the above (1) or (2), the average particle size of the roughness forming particles is 3 μm or more and 30 μm or less.

[0021] (4) Preferably, in any one of (1) to (3) above, the material of the roughness forming particles is any one of polyurethane, polyamide, and acrylic resin.

[0022] (5) Preferably, in any one of the above (1) to (4), the thickness of the binder polymer covering the roughness-forming particles on the groove portion is thicker than the thickness of the binder polymer covering the roughness-forming particles on the planar portion.

[0023] (6) Preferably, in any one of the above (1) to (5), the difference between the thickness of the binder polymer covering the roughness-forming particles on the planar portion and the thickness of the binder polymer covering the roughness-forming particles on the groove portion is greater than 4 μm and less than 16 μm.

[0024] (7) Preferably, in any one of (1) to (6) above, the elastic layer includes at least one of isoprene rubber, nitrile rubber, and epichlorohydrin rubber.

[0025] (8) Preferably, in any one of (1) to (7) above, the binder polymer of the surface layer is any one of polyurethane and polyamide.

[0026] (9) Preferably, in any one of the above (1) to (8), the roughness forming particles are composed of one type of particles.

[0027] (10) Preferably, in any one of the above (1) to (9), a mesh-like groove portion is formed on the outer peripheral surface of the elastomer layer, which is formed by intersecting groove portions extending in a direction within +46° relative to the circumferential direction and groove portions extending in a direction within -46° relative to the circumferential direction.

[0028] Effects of the Invention

[0029] According to the present invention, a charging roller for an electronic photographic device comprises a shaft, an elastomer layer formed on the outer peripheral surface of the shaft, and a surface layer formed on the outer peripheral surface of the elastomer layer, wherein one or more grooves extending in a direction within ±46° relative to the circumferential direction are regularly formed on the outer peripheral surface of the elastomer layer in the axial direction, the groove width w1 of the groove portion is greater than 4 μm and less than 30 μm, the groove depth of the groove portion is greater than 2 μm and less than 12 μm, the width w2 of the planar portion of the outer peripheral surface of the elastomer layer, which is a portion other than the groove portion, is greater than 4 μm and less than 30 μm, the relationship between the angle θ of the extending direction of the groove portion with respect to the circumferential direction and the ratio w2 / w1 of the groove width w1 of the groove portion and the width w2 of the planar portion is in the relationship (A) to (C) above, and the surface layer contains a binder polymer and roughness forming particles, and the roughness forming particles are respectively arranged on the planar portion and the groove portion of the elastomer layer, so that the uniformity of the discharge characteristics is excellent.

[0030] When the surface roughness Rz of the surface layer in the region on the groove portion is 2 μm to 16 μm and the surface roughness Rz of the entire surface layer is 5 μm to 26 μm, an appropriate discharge space and a discharge starting point can be formed between the photoreceptor and the charging roller.

[0031] When the average particle size of the roughness forming particles is 3 μm or more and 30 μm or less, appropriate concavities and convexities can be easily formed, thereby improving the uniformity of discharge characteristics.

[0032] If the material of the roughness-forming particles is any one of polyurethane, polyamide, and acrylic resin, the roughness-forming particles are made of a material having a high dielectric constant, and thus the charging property of the roller surface is improved.

[0033] If the thickness of the binder polymer covering the roughness-forming particles on the groove portion is thicker than the thickness of the binder polymer covering the roughness-forming particles on the planar portion, the discharge amount on the roughness-forming particles on the groove portion can be adjusted to be the same as the discharge amount on the roughness-forming particles on the planar portion, thereby improving the uniformity of the discharge characteristics.

[0034] If the difference between the thickness of the binder polymer covering the roughness forming particles on the plane portion and the thickness of the binder polymer covering the roughness forming particles on the groove portion is 4 μm or more, the surface charge of the binder polymer covering the roughness forming particles on the plane portion becomes relatively large, and the range of environments where no black spot images are generated is expanded. In addition, if the difference in thickness is 16 μm or less, it can be maintained at an appropriate thickness, so it is easy to form appropriate concavities and convexities. As a result, the uniformity of the discharge characteristics can be improved.

[0035] When the elastic layer includes at least one of isoprene rubber, nitrile rubber, and epichlorohydrin rubber, the compression set is small, and the generation of a streak image corresponding to a deformed portion when the charging roller is installed can be suppressed.

[0036] If the binder polymer of the surface layer is any one of polyurethane and polyamide, the binder polymer is composed of a material with a high dielectric constant, so the charging property of the roller surface is improved. In addition, the compression permanent deformation is small, and the generation of a striped image corresponding to the deformed portion when the charging roller is set can be suppressed.

[0037] If the roughness forming particles are composed of one type of particles, it is easy to reflect the concavo-convex shape of the elastomer layer to the surface concavo-convex of the charging roller, so it is easy to control the surface concavo-convex of the charging roller. In addition, since it is easy to control the agglomeration of the roughness forming particles, the uniformity of the surface roughness can be improved. Furthermore, since it is easy to adjust the thickness of the binder polymer covering the roughness forming particles, the uniformity of the discharge characteristics can be improved.

[0038] If a mesh-like groove portion formed by intersecting a groove portion extending in a direction within +46° relative to the circumferential direction and a groove portion extending in a direction within -46° relative to the circumferential direction is formed on the outer peripheral surface of the elastic layer, the uniformity of the surface roughness is improved. Thus, the uniformity of the discharge characteristics can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 (a) is a schematic diagram of the appearance of a charging roller for an electrophotographic device according to one embodiment of the present invention, Figure 1 (b) in the figure is its AA line cross-sectional view.

[0040] Figure 2 It is a schematic external view of the elastic layer showing the shape of the groove portion formed on the outer peripheral surface of the elastic layer.

[0041] Figure 3 It is a schematic external view of the elastic layer showing a modified example of the shape of the groove portion formed on the outer peripheral surface of the elastic layer.

[0042] Figure 4 It is an enlarged cross-sectional view of the surface.

[0043] Figure 5 It is a schematic external view of the elastic layer showing a modified example of the shape of the groove portion formed on the outer peripheral surface of the elastic layer. DETAILED DESCRIPTION

[0044] The charging roller for an electrophotographic apparatus (hereinafter, sometimes simply referred to as a charging roller) according to the present invention will be described in detail. Figure 1 1 and 1. (a) is a schematic diagram of the appearance of a charging roller for an electrophotographic device according to an embodiment of the present invention, and (b) is a cross-sectional view taken along line AA thereof. Figure 2 It is a schematic external view of the elastic layer showing the shape of the groove portion formed on the outer peripheral surface of the elastic layer. Figure 3 It is a schematic external view of the elastic layer showing a modified example of the shape of the groove portion formed on the outer peripheral surface of the elastic layer. Figure 4 It is an enlarged cross-sectional view of the surface.

[0045] The charging roller 10 includes a shaft 12, an elastomer layer 14 formed on the outer peripheral surface of the shaft 12, and a surface layer 16 formed on the outer peripheral surface of the elastomer layer 14. The elastomer layer 14 is a layer (base layer) that becomes a base of the charging roller 10. The surface layer 16 is a layer that appears on the surface of the charging roller 10. In addition, although not specifically shown in the figure, an intermediate layer such as a resistance adjustment layer can also be formed between the elastomer layer 14 and the surface layer 16 as needed.

[0046] The shaft body 12 is not particularly limited as long as it has conductivity. Specifically, examples thereof include a core rod made of a solid or hollow body made of a metal such as iron, stainless steel, or aluminum. An adhesive, a primer, or the like may be applied to the surface of the shaft body 12 as required. In other words, the elastomer layer 14 may also be bonded to the shaft body 12 via an adhesive layer (primer layer). The adhesive, the primer, or the like may also be made conductive as required.

[0047] exist Figure 2 , Figure 3 In FIG. 1 , the x (direction) is the axial direction of the charged roller 10, and the y (direction) is the circumferential direction of the charged roller 10. Figure 2 , Figure 3 As shown, one or more grooves 22 extending in a direction within ±46° relative to the circumferential direction y are regularly formed on the outer peripheral surface of the elastic layer 14 in the axial direction x. Figure 2 The outer peripheral surface of the elastic layer 14 is regularly formed with two or more grooves 22 extending in a direction of 0° relative to the circumferential direction y (extending in the circumferential direction) in the axial direction x. Figure 2 In the embodiment, one groove portion 22 is connected in a circular manner and is not formed in a spiral shape. Figure 3 The outer peripheral surface of the elastic layer 14 is regularly formed with one or more grooves 22 extending in a direction (the direction of θ) other than 0° and within ±46° relative to the circumferential direction y in the axial direction x. Figure 3 In the embodiment, the surrounding grooves 22 are not formed in a spiral shape, but are more than two. Figure 3 In the embodiment, the spiral grooves 22 are connected as a whole and thus are one. Regular means that the grooves 22 are formed at regular intervals in the axial direction x. On the outer peripheral surface of the elastic layer 14, the portion other than the grooves 22 is a flat surface 24. Figure 4 As shown, the plane portion 24 protrudes radially outward from the bottom surface 221 of the groove portion 22. The elastomer layer 14 is formed with surface irregularities on the outer peripheral surface by the bottom surface 221 of the groove portion 22 relatively arranged on the radial inner side and the plane portion 24 relatively arranged on the radial outer side. Moreover, since one or more groove portions 22 extending in a direction within ±46° relative to the circumferential direction y are regularly formed in the axial direction x, a uniform surface irregularities are formed on the outer peripheral surface of the elastomer layer 14. The direction within ±46° relative to the circumferential direction y refers to a direction in the range of -46° to 0° and 0° to 46° relative to the circumferential direction y.

[0048] The extension direction of the groove 22 is set to a direction within ±46° relative to the circumferential direction y because, if the angle of the extension direction of the groove 22 relative to the circumferential direction y becomes larger (the absolute value is an angle exceeding 46°), then when the photosensitive body and the charging roller 10 slide and rub, the edge (end edge) of the convex portion formed by the groove 22 is easily subjected to shear stress in the rotation direction (circumferential direction y) of the charging roller 10, and the convex portion is easily worn. If the convex portion is worn, the difference in charge between the concave and convex during durability becomes larger, and a striped image is easily generated. If the life of the electronic photographic equipment is extended, the charging roller 10 is also required to have longer durability, and the above-mentioned wear has a great impact.

[0049] If the extending direction of the groove 22 is set to a direction within ±46° relative to the circumferential direction y, when either the width of the convex portion formed by the groove 22 or the width of the groove 22 (groove width) becomes too large, the charging difference between the convex portion and the groove 22 within one cycle of the charging roller 10 is easily observed, which easily affects the uneven charging. Therefore, the ratio of the width of the convex portion to the width of the groove 22 (groove width) is set to a specific range, which suppresses the influence of uneven charging.

[0050] The groove width w1 of the groove portion 22 is greater than or equal to 4 μm and less than or equal to 30 μm. In addition, the groove depth d of the groove portion 22 is greater than or equal to 2 μm and less than or equal to 12 μm. The width w2 of the flat portion 24 is greater than or equal to 4 μm and less than or equal to 30 μm. Moreover, the angle θ of the extending direction of the groove portion 22 relative to the circumferential direction y and the ratio w2 / w1 of the groove width w1 of the groove portion 22 and the width w2 of the flat portion 24 are in a specific relationship.

[0051] If the groove width w1 of the groove portion 22 is less than 4 μm, the groove width w1 is too small, and the roughness forming particles 18 cannot enter the groove portion 22. Therefore, the difference between the surface roughness Rz caused by the roughness forming particles 18b on the plane portion 24 and the surface roughness Rz caused by the roughness forming particles 18a on the groove portion 22 becomes smaller, resulting in horizontal stripes caused by insufficient charging. If roughness forming particles 18 of a size that can be accommodated in a small groove width w1 are used, it is impossible to form a roughness that ensures sufficient discharge. In addition, from this point of view, the groove width w1 of the groove portion 22 is preferably set to 5 μm or more, 10 μm or more, 20 μm or more, etc., according to the size of the average particle size of the roughness forming particles 18 used.

[0052] If the groove width w1 of the groove portion 22 exceeds 30 μm, as described above, poor image (vertical stripes) are likely to occur. In addition, if the groove width w1 of the groove portion 22 exceeds 30 μm, the groove width w1 is too large, and the roughness forming particles 18 cannot be evenly arranged in the groove portion 22. If the roughness forming particles 18 whose size matches the large groove width w1 are used, the convex portion caused by the roughness forming particles 18 becomes too large, the surface roughness becomes too large, and the appropriate surface roughness cannot be formed. As a result, uniform discharge characteristics cannot be obtained. In addition, if the groove width w1 is too large, the binder polymer 16a of the roughness forming particles 18 covering the groove portion 22 is easy to contact the photoreceptor, so that not only the binder polymer 16a covering the roughness forming particles 18b on the flat surface portion 24 and the roughness forming particles 18b thereunder are worn, but also the binder polymer 16a covering the roughness forming particles 18a on the groove portion 22 and the roughness forming particles 18a thereunder are worn, so that the entire surface of the surface layer 16 is worn during durability, and uneven images are generated. In addition, from this point of view, the groove width w1 of the groove portion 22 is preferably set to 25 μm or less, 20 μm or less, 15 μm or less, 10 μm or less, etc., depending on the size of the average particle size of the roughness forming particles 18 used.

[0053] If the groove depth d of the groove portion 22 is less than 2 μm, the groove depth d is too small, and the difference between the surface roughness Rz caused by the roughness forming particles 18b on the plane portion 24 and the surface roughness Rz caused by the roughness forming particles 18a on the groove portion 22 becomes too small, resulting in horizontal stripes caused by insufficient charging. If a small roughness forming particle 18 is used in combination with a small groove depth d, it is impossible to form a roughness that ensures sufficient discharge. In addition, from this point of view, the groove depth d of the groove portion 22 is preferably set to 3 μm or more, 5 μm or more, 10 μm or more, etc., depending on the size of the average particle size of the roughness forming particles 18 used.

[0054] If the groove depth d of the groove portion 22 exceeds 12 μm, the groove depth d is too large, and the surface roughness cannot be formed on the groove portion 22 by the roughness forming particles 18 arranged in the groove portion 22. Therefore, black spots (gray fog) appear in the image after durability. In addition, if the groove depth d of the groove portion 22 exceeds 12 μm, the groove depth d is too large, and the difference between the surface roughness Rz caused by the roughness forming particles 18b on the plane portion 24 and the surface roughness Rz caused by the roughness forming particles 18a on the groove portion 22 becomes too large, and the difference in charging becomes large, so it is easy to produce image defects (vertical stripes). If a large roughness forming particle 18 is used in combination with a large groove depth d, the difference between the surface roughness Rz caused by the roughness forming particles 18b on the plane portion 24 and the surface roughness Rz caused by the roughness forming particles 18a on the groove portion 22 becomes too large, and it becomes difficult to discharge. From this viewpoint, the groove depth d of the groove portion 22 is preferably set to 10 μm or less, 8 μm or less, or the like, depending on the average particle size of the roughness forming particles 18 used.

[0055] The width w2 of the plane portion 24 is set to be the same as the groove width w1 of the groove portion 22, which is 4 μm or more and 30 μm or less in order to ensure uniform charging by making the width range the same as the groove width w1 of the groove portion 22. The width w2 of the plane portion 24 is preferably set to be 5 μm or more, 10 μm or more, 20 μm or more, 25 μm or less, 20 μm or less, 15 μm or less, 10 μm or less, etc., in accordance with the groove width w1 of the groove portion 22.

[0056] The relationship between the angle θ of the extension direction of the groove 22 and the ratio w2 / w1 of the width is in the following relationship (A) to (C). By being in the following relationship, the generation of striped images caused by the wear of the convex portion (flat portion 24) formed by the groove 22 and the uneven charging caused by the charging difference between the convex portion and the groove 22 within one cycle of the charging roller 10 can be suppressed.

[0057] (A) -5°≤θ≤+5°, 0.7≤w2 / w1≤1.3

[0058] (B) When -22°≤θ<-5° or +5°<θ≤+22°, 1.0≤w2 / w1≤2.0

[0059] (C) When -46°≤θ<-22° or +22°<θ≤+46°, 1.2≤w2 / w1≤2.6.

[0060] The outer peripheral surface of the elastic layer 14 is photographed using a laser microscope, and the angle of the groove portion 22 is calculated based on the average of the angles relative to the circumferential direction y at 100 points of the groove portion observed in the photographed image. The outer peripheral surface of the elastic layer 14 is photographed using a laser microscope, and the groove width w1 of the groove portion 22 is calculated based on the average of the groove width w1 at 100 points of the groove portion 22 observed in the photographed image. The radial cross-section of the elastic layer 14 is photographed using a laser microscope, and the groove depth d of the groove portion 22 is calculated based on the average of the groove depth d at 100 points of the groove portion 22 observed in the photographed image. The outer peripheral surface of the elastic layer 14 is photographed using a laser microscope, and the groove width w2 of the plane portion 24 is calculated based on the average of the width w2 at 100 points of the plane portion 24 observed in the photographed image.

[0061] The elastic layer 14 contains a crosslinked rubber. The elastic layer 14 is formed of a conductive rubber composition containing an uncrosslinked rubber. The crosslinked rubber is obtained by crosslinking the uncrosslinked rubber. The uncrosslinked rubber may be a polar rubber or a non-polar rubber.

[0062] Polar rubber is a rubber having a polar group, and polar groups include chloro group, nitrile group, carboxyl group, epoxy group, etc. As polar rubber, specifically, epichlorohydrin rubber, nitrile rubber (NBR), urethane rubber (U), acrylic rubber (copolymer of acrylate and 2-chloroethyl vinyl ether, ACM), chloroprene rubber (CR), epoxidized natural rubber (ENR), etc. Among polar rubbers, epichlorohydrin rubber and nitrile rubber (NBR) are more preferred from the viewpoint that volume resistivity is particularly easy to become low.

[0063] Examples of the epichlorohydrin rubber include epichlorohydrin homopolymers (CO), epichlorohydrin-ethylene oxide copolymers (ECO), epichlorohydrin-allyl glycidyl ether copolymers (GCO), and epichlorohydrin-ethylene oxide-allyl glycidyl ether terpolymers (GECO).

[0064] As urethane rubber, polyether-type urethane rubber having an ether bond in the molecule can be cited. Polyether-type urethane rubber can be produced by reacting a polyether having hydroxyl groups at both ends with a diisocyanate. As polyether, there is no particular limitation, and polyethylene glycol, polypropylene glycol, etc. can be cited. As diisocyanate, there is no particular limitation, and toluene diisocyanate, diphenylmethane diisocyanate, etc. can be cited.

[0065] Examples of non-polar rubbers include silicone rubber (Q), isoprene rubber (IR), natural rubber (NR), styrene-butadiene rubber (SBR), butadiene rubber (BR), etc. Among non-polar rubbers, silicone rubber is more preferred from the viewpoints of low hardness and resistance to aging (excellent elastic recovery).

[0066] The elastic layer 14 preferably includes at least one of isoprene rubber, nitrile rubber, and epichlorohydrin rubber. If the elastic layer 14 includes at least one of isoprene rubber, nitrile rubber, and epichlorohydrin rubber, the compression set is small, and the generation of a striped image corresponding to the deformed portion when the charging roller 10 is set can be suppressed.

[0067] Examples of the crosslinking agent include sulfur crosslinking agents, peroxide crosslinking agents, and dechlorination crosslinking agents. These crosslinking agents may be used alone or in combination of two or more.

[0068] Examples of the sulfur crosslinking agent include conventionally known sulfur crosslinking agents such as powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, sulfur chloride, thiuram-based vulcanization accelerators, and polymer polysulfides.

[0069] Examples of the peroxide crosslinking agent include conventionally known peroxide crosslinking agents such as peroxyketal, dialkyl peroxide, peroxyester, ketone peroxide, peroxydicarbonate, diacyl peroxide, and hydroperoxide.

[0070] Examples of the dechlorination crosslinking agent include dithiocarbonate compounds, and more specifically, include quinoxaline-2,3-dithiocarbonate, 6-methylquinoxaline-2,3-dithiocarbonate, 6-isopropylquinoxaline-2,3-dithiocarbonate, and 5,8-dimethylquinoxaline-2,3-dithiocarbonate.

[0071] The amount of the crosslinking agent is preferably within a range of 0.1 to 2 parts by mass, more preferably 0.3 to 1.8 parts by mass, and even more preferably 0.5 to 1.5 parts by mass, based on 100 parts by mass of the uncrosslinked rubber, from the viewpoint of preventing bleeding.

[0072] When a dechlorinating crosslinking agent is used as a crosslinking agent, a dechlorinating crosslinking accelerator may be used in combination. Examples of dechlorinating crosslinking accelerators include 1,8-diazabicyclo-(5.4.0)-undec-7-ene (hereinafter referred to as DBU) or its weak acid salt. The dechlorinating crosslinking accelerator may be used in the form of DBU, but from the perspective of its handling, it is preferably used in the form of its weak acid salt. Examples of weak acid salts of DBU include carbonates, stearates, 2-ethylhexanoates, benzoates, salicylates, 3-hydroxy-2-naphthoates, phenolic resin salts, 2-mercaptobenzothiazole salts, 2-mercaptobenzimidazole salts, and the like.

[0073] The content of the dechlorination crosslinking accelerator is preferably within a range of 0.1 to 2 parts by mass, more preferably 0.3 to 1.8 parts by mass, and even more preferably 0.5 to 1.5 parts by mass, based on 100 parts by mass of the uncrosslinked rubber, from the viewpoint of preventing bleeding.

[0074] In order to impart conductivity, a conductive agent may be added to the elastomer layer 14. Examples of the conductive agent include electronic conductive agents and ionic conductive agents. Examples of electronic conductive agents include carbon black, graphite, and conductive metal oxides. Examples of conductive metal oxides include conductive titanium oxides, conductive zinc oxides, and conductive tin oxides. Examples of ionic conductive agents include quaternary ammonium salts, borates, and surfactants. In addition, various additives may be appropriately added to the elastomer layer 14 as needed. Examples of additives include lubricants, vulcanization accelerators, antioxidants, light stabilizers, viscosity modifiers, processing aids, flame retardants, plasticizers, foaming agents, fillers, dispersants, defoaming agents, pigments, and release agents.

[0075] The volume resistivity of the elastic layer 14 can be adjusted to a predetermined value by the type of crosslinked rubber, the amount of ion conductive agent, the amount of electronic conductive agent, etc. The volume resistivity of the elastic layer 14 is appropriately set to 10 2 ~10 10 Ω·cm, 10 3 ~10 9 Ω·cm, 10 4 ~10 8 The range of Ω·cm or the like may be sufficient.

[0076] The thickness of the elastic layer 14 is not particularly limited, and may be appropriately set within a range of 0.1 to 10 mm, etc., depending on the intended use.

[0077] The surface layer 16 includes a binder polymer 16 a and roughness-forming particles 18 .

[0078] The binder polymer 16a is a base polymer constituting the surface layer 16. Examples of the binder polymer 16a include urethane resin, polyamide resin, acrylic resin, acrylic silicone resin, butyral resin (PVB), alkyd resin, polyester resin, fluororubber, fluororesin, a mixture of fluororubber and fluororesin, silicone resin, silicone grafted acrylic polymer, acrylic grafted silicone polymer, nitrile rubber, urethane rubber, and the like.

[0079] The adhesive polymer 16a is preferably any one of polyurethane and polyamide. If the adhesive polymer 16a of the surface layer 16 is any one of polyurethane and polyamide, the adhesive polymer 16a is composed of a material with a high dielectric constant, so the charging property of the roller surface is improved. In addition, the compression permanent deformation is small, and the generation of a striped image corresponding to the deformed portion when the charging roller 10 is set can be suppressed. Polyurethane includes carbamate resin, carbamate rubber, and carbamate elastomer. Polyamide can be a modified polyamide. As modified polyamides, alkoxylated polyamides such as N-methoxymethylated nylon and the like can be listed.

[0080] The roughness forming particles 18 are particles for providing roughness to the surface of the surface layer 16. In other words, they are particles for providing unevenness to the surface of the surface layer 16. Figure 4 As shown, the roughness forming particles 18 are respectively arranged on the plane portion 24 and the groove portion 22 of the elastomer layer 14. Due to the height difference between the plane portion 24 of the elastomer layer 14 and the bottom surface 221 of the groove portion 22, the roughness forming particles 18b on the plane portion 24 (the roughness forming particles 18b arranged on the plane portion 24) and the roughness forming particles 18a on the groove portion 22 (the roughness forming particles 18a arranged on the groove portion 22) have different degrees of protrusion to the radial outside even if they have the same particle size. Due to the height difference between the plane portion 24 of the elastomer layer 14 and the bottom surface 221 of the groove portion 22, the roughness forming particles 18b on the plane portion 24 protrude radially outward more than the roughness forming particles 18a on the groove portion 22.

[0081] The convex portion formed by the roughness forming particles 18b on the plane portion 24 and protruding further radially outward is formed as a portion in contact with the photoreceptor, and the convex portion formed by the roughness forming particles 18a on the groove portion 22 and located further inward in the radial direction is formed as a portion not in contact with the photoreceptor. The convex portion formed by the roughness forming particles 18a on the groove portion 22 is formed as a starting point for discharge. The surface layer 16 includes the roughness forming particles 18b on the plane portion 24, thereby ensuring an appropriate discharge space between the photoreceptor and the charging roller 10. In addition, the surface layer 16 includes the roughness forming particles 18a on the groove portion 22, thereby ensuring a starting point for discharge. In this way, the surface unevenness of the surface layer 16 increases the discharge space between the photoreceptor and the charging roller 10, thereby promoting discharge. As a result, the charging performance can be improved and image problems such as horizontal stripes and unevenness can be suppressed. In the charged roller 10 involved in the present invention, due to the presence of a height difference between the planar portion 24 of the elastomer layer 14 and the bottom surface 221 of the groove portion 22, even if the roughness forming particles 18 contained in the surface layer 16 have the same particle size, an appropriate discharge space and a starting point for discharge can be easily formed between the photosensitive body and the charged roller 10.

[0082] The surface roughness Rz of the surface layer 16 in the region M on the groove portion 22 is preferably set to be 2 μm or more and 16 μm or less. In addition, the surface roughness Rz of the entire surface layer 16 is preferably set to be 5 μm or more and 26 μm or less. This can form an appropriate discharge space and a starting point for discharge between the photoreceptor and the charging roller 10.

[0083] If the surface roughness Rz of the surface layer 16 in the area M on the groove portion 22 is less than 2 μm, the surface roughness Rz is too small, the starting point of the discharge is insufficient, the discharge becomes insufficient, and sometimes black spots (gray fog) cannot be suppressed in the image after durability. In addition, from this point of view, the surface roughness Rz is more preferably 3 μm or more, and more preferably 5 μm or more. On the other hand, if the surface roughness Rz of the surface layer 16 in the area M on the groove portion 22 exceeds 16 μm, the surface roughness Rz of the entire surface layer 16 becomes too large, it becomes difficult to discharge, and sometimes black spots (gray fog) cannot be suppressed in the image after durability. In addition, from this point of view, the surface roughness Rz is more preferably 15 μm or less, and more preferably 12 μm or less.

[0084] If the surface roughness Rz of the entire surface layer 16 is less than 5μm, the surface roughness Rz is too small, the starting point of discharge is insufficient, the discharge becomes insufficient, and sometimes black spots (gray fog) cannot be suppressed in the image after durability. In addition, from this point of view, the surface roughness Rz is more preferably 7μm or more, and more preferably 10μm or more. On the other hand, if the surface roughness Rz of the entire surface layer 16 exceeds 26μm, the surface roughness Rz becomes too large, it becomes difficult to discharge, and sometimes black spots (gray fog) cannot be suppressed in the image after durability. In addition, from this point of view, the surface roughness Rz is more preferably 25μm or less, and more preferably 20μm or less.

[0085] The surface roughness Rz is a 10-point average roughness, which is the average value of the values ​​measured at any five locations in accordance with JIS B0601 (1994). The surface roughness Rz of the entire surface layer 16 can be measured by observation using a laser microscope (such as "VK-9510" manufactured by KEYENCE). In the image taken at 400 times, the value calculated in the surface roughness mode in the analysis program (program name KEYENCE VKAnalyzer analysis application) can be used as the surface roughness Rz of the entire surface layer 16. The surface roughness Rz of the surface layer 16 in the area on the groove 22 can be measured by observation using a laser microscope (such as "VK-9510" manufactured by KEYENCE). In the captured image, it is possible to select 0.01mm in the surface roughness mode in the analysis program (program name KEYENCE VKAnalyzer analysis application). 2The value calculated based on the groove portion is taken as the surface roughness Rz of the surface layer 16 in the area above the groove portion 22.

[0086] The surface roughness Rz of the surface layer 16 can be adjusted by adjusting the groove width w1 and groove depth d of the groove portion 22 , the width w2 of the flat portion 24 , the particle size of the roughness forming particles 18 , the thickness of the binder polymer 16 a , and the like.

[0087] As the roughness forming particles 18, particles such as resin particles and inorganic particles can be used as the roughness forming particles 18 added to the surface layer 16 of the charging roller. The material of the roughness forming particles 18 is not particularly limited. As the material of the roughness forming particles 18, any one of polyurethane, polyamide, and acrylic resin is preferred. If the material of the roughness forming particles 18 is any one of polyurethane, polyamide, and acrylic resin, the roughness forming particles 18 are composed of a material with a high dielectric constant, so the charging property of the roller surface is improved.

[0088] The size of the roughness forming particles 18 is not particularly limited. From the viewpoint of forming appropriate concavities and convexities and improving the uniformity of discharge characteristics, the average particle size is preferably 3 μm or more and 30 μm or less. The average particle size is more preferably 5 μm or more and 30 μm or less, and the average particle size is further preferably 10 μm or more and 30 μm or less. The average particle size of the roughness forming particles 18 is expressed as the average value of any 20 points by observing the surface of the surface layer 16 with a laser microscope and taking the diameter of the roughness forming particles 18 visible when observing the surface as the particle size.

[0089] The roughness forming particles 18 can be composed of one type of particles or of two or more types of particles. First, one type of particles refers to particles of the same material. The same material means that, among particles made of polymers, particles contained in polyurethane, for example, can be called the same within a wide range, and particles of the same monomer composition can be called the same within a narrow range. More preferably, particles of the same monomer composition are called the same within a narrow range. In addition, secondly, one type of particles refers to particles of the same particle size. The same particle size means that the particle size is uniform. For example, it means that the diameter of the roughness forming particles 18 is measured for 50 locations at any position, the average is set to μ, the deviation is set to σ, and μ / σ is less than 4.97. The diameter of the roughness forming particles 18 can be measured by observing the diameter of the particles using a laser microscope (such as "VK-9510" manufactured by KEYENCE).

[0090] The roughness forming particles 18 are preferably composed of one kind of particles. If the roughness forming particles 18 are composed of two or more particles with different materials and particle sizes, it is necessary to further consider the difference in the influence of the material and particle size of the roughness forming particles 18 on the discharge characteristics to adjust the thickness of the binder polymer 16a covering the roughness forming particles 18. If the roughness forming particles 18 are composed of one kind of particles in terms of material and particle size, it is easy to adjust the thickness of the binder polymer 16a covering the roughness forming particles 18. Thus, the uniformity of the discharge characteristics can be improved. In addition, in the case of containing two particles with greatly different particle sizes, the particles of different sizes are easy to agglomerate, and the dispersibility is easy to reduce. If the roughness forming particles 18 are composed of one kind of particles in terms of particle size, it is easy to control the agglomeration of the roughness forming particles 18, so that the uniformity of the surface roughness can be improved. In addition, if the roughness forming particles 18 are composed of one kind of particles in terms of particle size, it is easy to reflect the concave-convex shape of the elastomer layer 14 on the surface concave-convex of the charged roller, so it is easy to control the surface concave-convex of the charged roller.

[0091] In the surface layer 16, the thickness of the binder polymer 16a is preferably set to a predetermined thickness. The thickness t1 of the binder polymer 16a covering the roughness forming particles 18 on the groove portion 22 is preferably thicker than the thickness t2 of the binder polymer 16a covering the roughness forming particles 18 on the plane portion 24. As a result, the discharge amount on the roughness forming particles 18 on the groove portion 22 can be adjusted to be the same as the discharge amount on the roughness forming particles 18 on the plane portion 24, thereby improving the uniformity of the discharge characteristics. As a result, the generation of black spot images can be suppressed. This is because the portion where the roughness forming particles 18 on the plane portion 24 exist is grounded to the photoreceptor, so that the discharge amount is worse than the portion where the roughness forming particles 18 on the groove portion 22 exist. Therefore, in order to make the discharge amount the same at each position, it is necessary to make the film thickness of the portion where the roughness forming particles 18 on the plane portion 24 exist thinner than the portion where the roughness forming particles 18 on the groove portion 22 exist to increase the electrostatic capacitance, thereby increasing the amount of charge on the surface.

[0092] The difference (t1-t2) between the thickness t1 of the binder polymer 16a of the roughness-forming particles 18 covering the groove portion 22 and the thickness t2 of the binder polymer 16a of the roughness-forming particles 18 covering the plane portion 24 is preferably 4 μm or more and 16 μm or less. If the above-mentioned thickness difference (t1-t2) is 4 μm or more, the surface charge amount of the binder polymer 16a of the roughness-forming particles 18 covering the plane portion 24 becomes relatively large, and the range of environments where no black spot images are generated is expanded. From this point of view, the above-mentioned thickness difference (t1-t2) is more preferably 5 μm or more, and more preferably 6 μm or more. In addition, if the above-mentioned thickness difference (t1-t2) is less than 16 μm, it can be maintained at an appropriate thickness, so it is easy to form appropriate bumps and depressions. As a result, the uniformity of the discharge characteristics can be improved. From this point of view, the above-mentioned thickness difference (t1-t2) is more preferably 15 μm or less, and more preferably 12 μm or less.

[0093] The thickness t1 of the binder polymer 16a covering the roughness forming particles 18 on the groove portion 22 is preferably 5 μm or more and 20 μm or less. If the thickness t1 is 5 μm or more, the resistance of the discharge portion is easy to become uniform, and the discharge characteristics are easy to become uniform. In addition, from this point of view, the thickness t1 is more preferably 6 μm or more, and more preferably 7 μm or more. Moreover, if the thickness t1 is 20 μm or less, the surface of the surface layer 16 on the groove portion 22 is ensured to have a moderate roughness, and the discharge area can be ensured. In addition, from this point of view, the thickness t1 is more preferably 18 μm or less, and more preferably 15 μm or less.

[0094] The thickness t2 of the binder polymer 16a covering the roughness-forming particles 18 on the plane portion 24 is preferably 1.0 μm or more and 4.0 μm or less. If the thickness t2 is 1.0 μm or more, the resistance of the discharge portion is easy to become uniform, and the discharge characteristics are easy to become uniform. In addition, from this point of view, the thickness t2 is more preferably 1.5 μm or more, and more preferably 2.0 μm or more. Moreover, if the thickness t2 is 4.0 μm or less, a moderate roughness is ensured on the surface of the surface layer 16, and the discharge area can be ensured. In addition, from this point of view, the thickness t2 is more preferably 3.5 μm or less, and more preferably 3.0 μm or less.

[0095] The thickness t1 and t2 of the binder polymer 16a can be measured by observing the cross section using a laser microscope (e.g., "VK-9510" manufactured by KEYENCE). For example, the thickness of the binder polymer 16a is measured at five locations of any position of the binder polymer 16a covering the roughness forming particles 18 on the groove portion 22, and t1 can be represented by the average thereof. In addition, the thickness of the binder polymer 16a is measured at five locations of any position of the binder polymer 16a covering the roughness forming particles 18 on the flat portion 24, and t2 can be represented by the average thereof.

[0096] In order to make the thickness t1 of the binder polymer 16a covering the roughness forming particles 18 on the groove portion 22 thicker than the thickness t2 of the binder polymer 16a covering the roughness forming particles 18 on the flat portion 24, it is preferable to utilize both the instability of the surface energy of the roughness forming particles 18 on the groove portion 22 and the instability of the energy of the matrix rubber of the groove portion 22. In other words, it is preferable to utilize the fact that the roughness forming particles 18 on the groove portion 22 are likely to be coated with a large amount of the binder polymer 16a for stabilization, and the fact that the matrix rubber of the groove portion 22 is likely to be coated with a large amount of the binder polymer 16a for stabilization.

[0097] The content of the roughness forming particles 18 in the surface layer 16 is not particularly limited, but is preferably 3 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the binder polymer 16a of the surface layer 16, from the viewpoint of improving the dispersibility of the roughness forming particles 18 and facilitating ensuring uniform charging properties. More preferably, it is 5 parts by mass or more and 30 parts by mass or less.

[0098] In order to impart conductivity, a conductive agent may be added to the surface layer 16. Conductive agents include electronic conductive agents and ionic conductive agents. Electronic conductive agents include carbon black, graphite, and conductive metal oxides. Conductive metal oxides include conductive titanium oxides, conductive zinc oxides, and conductive tin oxides. Ionic conductive agents include quaternary ammonium salts, borates, and surfactants. In addition, various additives may be appropriately added to the surface layer 16 as needed. Additives include plasticizers, leveling agents, fillers, vulcanization accelerators, processing aids, and release agents.

[0099] From the viewpoint of chargeability, etc., the volume resistivity of the surface layer 16 is preferably set in the semi-conductive region. Specifically, for example, it is preferably set at 1.0×10 7 ~1.0×10 10 The volume resistivity can be measured in accordance with JIS K6911.

[0100] The elastic layer 14 can be formed, for example, as follows: First, the shaft 12 is coaxially disposed in the hollow portion of a roll forming mold, an uncrosslinked conductive rubber composition is injected, and the uncrosslinked conductive rubber composition is heated, cured (crosslinked), and then demolded, or the uncrosslinked conductive rubber composition is extruded on the surface of the shaft 12, thereby forming the elastic layer 14 on the outer periphery of the shaft 12.

[0101] As methods for forming the groove portion 22 on the outer peripheral surface of the elastomer layer 14, grinding, mold forming, etc. can be cited. In any method, it is possible to form a regular groove portion 22 on the outer peripheral surface of the elastomer layer 14. In the case of utilizing grinding, when forming a circumferential groove portion 22, it is preferably performed by a cut-in method. When forming a spiral groove portion 22, it is preferably performed by a transverse method. The transverse method can form a groove portion 22 that regularly describes a spiral along the axial direction on the outer peripheral surface of the elastomer layer 14, for example, by rotating a roller having the elastomer layer 14 around the center of the axis at a constant speed while moving a grinding wheel in contact with the outer peripheral surface of the elastomer layer 14 in the axial direction on one side at a constant speed.

[0102] The surface layer 16 can be formed by using a material for forming the surface layer 16, applying it to the outer peripheral surface of the elastomer layer 14, and appropriately performing a drying treatment. The material for forming the surface layer 16 may contain a diluent solvent. Examples of the diluent solvent include ketone solvents such as methyl ethyl ketone (MEK) and methyl isobutyl ketone, alcohol solvents such as isopropyl alcohol (IPA), methanol, and ethanol, hydrocarbon solvents such as hexane and toluene, acetic acid solvents such as ethyl acetate and butyl acetate, ether solvents such as diethyl ether and tetrahydrofuran, and water.

[0103] According to the charging roller 10 constructed as above, one or more grooves 22 extending in a direction within ±46° relative to the circumferential direction are regularly formed in the axial direction on the outer peripheral surface of the elastomer layer 14, and the groove width w1, groove depth d and width w2 of the plane portion 24 of the groove portion 22 are within a specific range, and the angle θ of the extending direction of the groove portion 22 relative to the circumferential direction and the ratio w2 / w1 of the groove width w1 of the groove portion 22 to the width w2 of the plane portion 24 are in a specific relationship, thereby making it possible to evenly and evenly arrange the roughness forming particles 18 on both the plane portion 24 and the groove portion 22 of the elastomer layer 14, and to form an appropriate surface roughness and form an appropriate roughness difference between the plane portion 24 and the groove portion 22 of the elastomer layer 14, thereby adjusting to an appropriate discharge amount. Therefore, the uniformity of the discharge characteristics is excellent. Furthermore, the discharge amount can be made uniform by making the thickness of the binder polymer 16a covering the roughness-forming particles 18 on the groove portion 22 thicker than the thickness of the binder polymer 16a covering the roughness-forming particles 18 on the flat surface portion 24. Therefore, the uniformity of the discharge characteristics is excellent.

[0104] The charging roller 10 involved in the present invention is not formed with surface unevenness on the charging roller by arranging two kinds of roughness forming particles of different sizes on the outer peripheral surface of the overall flat elastomer layer, but is formed with surface unevenness on the charging roller 10 by forming a predetermined uneven shape on the outer peripheral surface of the elastomer layer 14 in advance, and arranging relatively uniform roughness forming particles 18 of a predetermined size in the uneven shape. The roughness forming particles 18 are arranged not only on the groove portion 22 of the elastomer layer 14, but also on the plane portion 24. Thus, the height difference of the surface unevenness of the elastomer layer 14 appears as the surface unevenness of the charging roller 10. If the roughness forming particles 18 are relatively uniform, the surface unevenness of the elastomer layer 14 is easily reflected on the surface of the charging roller 10. In order to arrange the roughness forming particles 18 not only on the groove portion 22 of the elastomer layer 14 but also on the plane portion 24, the groove width w1 of the groove portion 22 should not be too large or too small relative to the size of the roughness forming particles 18. By making the groove width w1 of the groove portion 22 a predetermined size, the roughness forming particles 18 can be reliably and evenly arranged not only on the groove portion 22 but also on the plane portion 24. Similarly, the width w2 of the plane portion 24 should not be too large or too small. In order to reliably and evenly arrange the roughness forming particles 18 on the plane portion 24, a predetermined area ratio is preferred. Moreover, in the present invention, a predetermined concave-convex shape is formed on the outer peripheral surface of the elastomer layer 14, thereby, the surface area of ​​the outer peripheral surface of the elastomer layer can be further increased compared to the outer peripheral surface of the elastomer layer that is flat as a whole. As a result, the ease of discharge is improved. This is an effect that can be exerted even if, for example, the groove portion 22 of the elastomer layer 14 is filled with the binder polymer 16a of the surface layer 16. This effect is a hitherto unknown insight. From this point of view, the advantages brought about by the construction of the present invention are also possessed.

[0105] The extension direction of the groove portion 22 is within ±46° relative to the circumferential direction y. Therefore, during the sliding friction between the photosensitive body and the charging roller 10, the edge (end edge) of the convex portion formed by the groove portion 22 is not easily subjected to the shear stress in the rotation direction (circumferential direction y) of the charging roller 10, thereby suppressing the wear of the convex portion. During the endurance, the difference in charge between the concave and convex portions caused by the wear of the convex portion is suppressed to a smaller value, thereby suppressing the generation of striped images. At this time, when either the width of the convex portion formed by the groove portion 22 or the width (groove width) of the groove portion 22 becomes too large, it is easy to observe the charge difference between the convex portion and the groove portion 22 within one circle of the charging roller 10, which is easy to affect the uneven charging. However, since the ratio of the width of the convex portion to the width (groove width) of the groove portion 22 is set to a specific range, the generation of uneven charging can be suppressed.

[0106] As mentioned above, although embodiment of this invention was described, this invention is not limited to the said embodiment, Various changes can be made within the range which does not deviate from the summary of this invention.

[0107] For example, in the above-mentioned embodiment, one or more grooves 22 extending in a direction within ±46° relative to the circumferential direction y are regularly formed on the outer peripheral surface of the elastic layer 14 in the axial direction x, but it may also be as follows. Figure 5 As shown, a mesh-like groove portion formed by the intersection of the groove portion 22 (22a) extending in a direction within +46° relative to the circumferential direction y and the groove portion 22 (22b) extending in a direction within -46° relative to the circumferential direction is formed on the outer peripheral surface of the elastic body layer 14. As a result, the uniformity of the surface roughness is improved, and the uniformity of the discharge characteristics can be improved.

[0108] Regarding the groove portion 22 formed in a spiral shape, it can be a groove portion having only a groove portion that depicts a spiral in a left-handed thread regularly along the axial direction, or it can be a groove portion having only a groove portion that depicts a spiral in a right-handed thread regularly along the axial direction, or it can be a mesh-like groove portion formed by intersecting a groove portion that depicts a spiral in a right-handed thread regularly along the axial direction and a groove portion that depicts a spiral in a left-handed thread regularly along the axial direction.

[0109] The spirally intersecting mesh-like grooves can be formed, for example, by moving the above-mentioned grinding wheel axially to one side and then axially to the other side, thereby forming a mesh-like groove 22 on the outer peripheral surface of the elastomer layer 14, in which grooves 22a that regularly describe a spiral in the manner of a right-hand thread along the axial direction and grooves 22b that regularly describe a spiral in the manner of a left-hand thread along the axial direction are intersected.

[0110] Example

[0111] Hereinafter, the present invention will be described in detail using Examples and Comparative Examples.

[0112] (Example 1)

[0113] <Preparation of Conductive Rubber Composition>

[0114] 30 parts by mass of carbon black, 6 parts by mass of zinc oxide, 2 parts by mass of stearic acid, 1 part by mass of sulfur, 0.5 parts by mass of a thiazole vulcanization accelerator, 0.5 parts by mass of a thiuram vulcanization accelerator, and 50 parts by mass of heavy calcium carbonate were added to 100 parts by mass of isoprene rubber, and the mixture was kneaded for 10 minutes using a closed mixer adjusted to 50° C. to prepare a conductive rubber composition.

[0115] As materials for the conductive rubber composition, the following materials were prepared.

[0116] ・Isoprene rubber (IR): "JSR IR2200" manufactured by JSR

[0117] Carbon black: "SHO BLACK N762" manufactured by Cabot Japan

[0118] Zinc oxide: "Zinc oxide type 2" manufactured by Sakai Chemical Industry

[0119] · Stearic acid: "SAKURA Stearate" manufactured by NOF Corporation

[0120] ・Sulfur: "Powdered sulfur" manufactured by Tsurumi Chemical Industry

[0121] Thiazole vulcanization accelerator: "NOCCELER DM" manufactured by Ouchi Shinko Chemical Industry

[0122] Thiuram-based vulcanization accelerator: "NOCCELER TRA" manufactured by Ouchi Shinko Chemical Industry

[0123] Heavy calcium carbonate: "Whiton B" manufactured by Shiraishi Calcium, average particle size 3.6μm

[0124] <Production of Elastomer Layer>

[0125] A core rod (8 mm in diameter) is placed in a forming mold (tubular), and the above composition is injected. After heating at 180°C for 30 minutes, the mixture is cooled and demolded, and an elastomer layer formed of a conductive rubber elastic body having a thickness of 1.9 mm is formed on the periphery of the core rod. Next, while the roller body having the elastomer layer is rotated around the axis at a certain speed, a grinding wheel in contact with the outer peripheral surface of the elastomer layer is moved axially in one direction at a certain speed, and then the grinding wheel in contact with the outer peripheral surface of the elastomer layer is moved axially in the other direction at a certain speed, thereby forming a mesh-like groove portion formed by crossing a groove portion that regularly draws a spiral in the manner of a right-handed thread along the axial direction and a groove portion that regularly draws a spiral in the manner of a left-handed thread along the axial direction on the outer peripheral surface of the elastomer layer. The conditions are as follows.

[0126] Roller rotation speed···500rpm

[0127] Grinding wheel moving speed···0.05m / s

[0128] Grinding wheel peripheral speed···72m / s

[0129] Grinding wheel grit number···#1500

[0130] Slot spacing···0.3mm

[0131] <Surface production>

[0132] The roughness forming particles, the binder polymer and the carbon black as the conductive agent were mixed in the manner of the mixed composition (parts by mass) described in the table, 200 parts by mass of methyl ethyl ketone (MEK) were added, and the mixture was mixed and stirred at a predetermined stirring speed to prepare a liquid composition for forming a surface layer. Then, while continuing to stir, the liquid composition was roll-coated on the outer peripheral surface of the elastomer layer and heat-treated to form a surface layer with a thickness of 1.0 μm on the outer periphery of the elastomer layer. Thus, the charged roller of Example 1 was prepared.

[0133] (Example 2)

[0134] <Preparation of Conductive Rubber Composition>

[0135] 0.7 parts by mass of stearic acid, 5 parts by mass of zinc oxide, 2 parts by mass of hydrotalcite, 3 parts by mass of a peroxide crosslinking agent, and 20 parts by mass of carbon were added to 100 parts by mass of NBR, and these were stirred and mixed in a stirrer to prepare a conductive rubber composition.

[0136] As materials for the conductive rubber composition, the following materials were prepared.

[0137] NBR: Nipol 1041 made by Japan Zeon

[0138] · Stearic acid: NOF Corporation's "Stearic Acid SAKURA"

[0139] Zinc oxide: "Zinc oxide type 2" manufactured by Sakai Chemical Industry

[0140] · Hydrotalcite: "DHT4A" manufactured by Kyowa Chemical Industry

[0141] ·Peroxide crosslinking agent: NOF Corporation's "PERCUMYL D40"

[0142] Carbon: Ketjen Black EC300J manufactured by Ketjen Black International

[0143] <Production of Elastomer Layer>

[0144] The heating temperature was changed to 170° C., and an elastic layer formed of a conductive rubber elastic body was formed in the same manner as in Example 1. Next, in the same manner as in Example 1, mesh-like grooves were formed on the outer peripheral surface of the elastic layer by polishing.

[0145] <Surface production>

[0146] A surface layer having a thickness of 1.0 μm was formed on the outer periphery of the elastic layer in the same manner as in Example 1. Thus, a charging roller of Example 2 was produced.

[0147] (Example 3)

[0148] <Preparation of Conductive Rubber Composition>

[0149] 5 parts by mass of a vulcanization aid, 10 parts by mass of carbon, 0.5 parts by mass of a vulcanization accelerator, 2 parts by mass of sulfur, and 50 parts by mass of a filler were added to 100 parts by mass of the epichlorohydrin rubber, and these were stirred and mixed with a stirrer to prepare a conductive rubber composition.

[0150] As materials for the conductive rubber composition, the following materials were prepared.

[0151] ·ECO (Hydrin H1100 made by Japan Zeon)

[0152] ・Vulcanizing accelerator (zinc oxide, "Zinc Oxide 2" manufactured by Mitsui Kinzoku Co., Ltd.)

[0153] Carbon ("KetjenBlack EC300J" manufactured by KetjenBlack International)

[0154] Vulcanization accelerator (2-mercaptobenzothiazole, "NOCCELER MP" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)

[0155] ・Sulfur (manufactured by Tsurumi Chemical Industry Co., Ltd., "SULFAX PTC")

[0156] Filler (calcium carbonate, "Hakuyanhua CC" manufactured by Shiraishi Industries)

[0157] <Production of Elastomer Layer>

[0158] An elastic layer made of a conductive rubber elastic body was formed in the same manner as in Example 1. Next, in the same manner as in Example 1, mesh-like grooves were formed on the outer peripheral surface of the elastic layer by polishing.

[0159] <Surface production>

[0160] A surface layer having a thickness of 1.0 μm was formed on the outer periphery of the elastic layer in the same manner as in Example 1. Thus, a charging roller of Example 3 was produced.

[0161] (Examples 4, 5, 7, 8)

[0162] The charging rollers of Examples 4, 5, 7 and 8 were produced in the same manner as in Example 3 by changing the surface layer material.

[0163] (Example 6)

[0164] A groove portion that regularly draws a left-hand spiral along the axial direction was formed on the outer peripheral surface of the elastic layer, and a charging roller of Example 6 was produced in the same manner as in Example 3.

[0165] (Example 9)

[0166] A charging roller of Example 9 was produced in the same manner as in Example 4 except that the grooves were formed in the circumferential direction.

[0167] (Example 10)

[0168] A charging roller of Example 10 was produced in the same manner as in Example 4 except that the formation angle of the groove portion was changed.

[0169] (Example 11)

[0170] A charging roller of Example 11 was produced in the same manner as in Example 6 except that the formation angle of the groove portion was changed.

[0171] (Example 12 to Example 15)

[0172] The ratio of the groove width of the groove portion to the width of the flat portion (w2 / w1) was changed, and a charging roller was produced in the same manner as in Examples 9 and 10.

[0173] (Example 16 to Example 23)

[0174] A charging roller was produced in the same manner as in Example 10 by changing the ratio of the groove width to the width of the flat portion (w2 / w1) and the angle at which the grooves were formed.

[0175] (Comparative Example 1 to Comparative Example 6)

[0176] A charging roller was produced in the same manner as in Example 4 by changing the groove width, the groove depth or the width of the flat surface.

[0177] (Comparative Example 7 to Comparative Example 14)

[0178] The ratio of the groove width of the groove portion to the width of the flat portion (w2 / w1) was changed, and a charging roller was produced in the same manner as in Examples 16 to 23.

[0179] (Comparative Example 15)

[0180] The formation angle of the groove portion was changed and a charging roller was produced in the same manner as in Example 23.

[0181] The materials used as the surface layer material are as follows.

[0182] · Binder polymer (PA): "FINE RESIN FR-101" manufactured by Lead City

[0183] ·Binder polymer (PU): "ART Resin UN-333" manufactured by Negami Industries

[0184] · Roughness forming particles (PU): "ART-pearl C-1000 transparent" manufactured by Negami Industries, average particle size 3 μm

[0185] · Roughness forming particles (PU): "ART-pearl C-200 transparent graded product" manufactured by Negami Industries, average particle size 30 μm

[0186] · Particles for roughness formation (PU): "ART-pearl C-300 transparent" manufactured by Negami Industries, average particle size 22 μm

[0187] · Roughness forming particles (PU): "ART-pearl C-300 transparent graded product" manufactured by Negami Industries, average particle size 20 μm

[0188] · Roughness forming particles (PU): "ART-pearl C-400 transparent" manufactured by Negami Industries, average particle size 15 μm

[0189] · Roughness forming particles (PU): "ART-pearl C-600 transparent" manufactured by Negami Industries, average particle size 11 μm

[0190] ・Roughness forming particles (PA): Toray's "TR-2" with an average particle size of 22 μm

[0191] · Particles for roughness formation (PMMA): "ART-pearl GR-200 transparent" manufactured by Negami Industries, average particle size 20 μm

[0192] Carbon black: "SEAST 9H" manufactured by Tokai Carbon

[0193] The surface analysis and cross-sectional analysis of the polished elastic layer of the charging roller were performed to calculate the groove width, groove depth, width of the flat portion, and angle of the groove. In addition, the surface roughness Rz and the thickness of the adhesive polymer of the surface layer of the produced charging roller were measured. In addition, the following evaluations were performed.

[0194] (Concavoconvex shape of elastic layer)

[0195] The outer peripheral surface of the elastomer layer is photographed using a laser microscope, and the groove width of the groove portion is calculated based on the average of the groove width of 100 points of any groove portion observed in the photographed image. The radial cross-section of the elastomer layer is photographed using a laser microscope, and the groove depth of the groove portion is calculated based on the average of the groove depth of 100 points of any groove portion observed in the photographed image. The outer peripheral surface of the elastomer layer is photographed using a laser microscope, and the width of the plane portion is calculated based on the average of the width of 100 points of any plane portion observed in the photographed image. The outer peripheral surface of the elastomer layer is photographed using a laser microscope, and the angle of the groove portion is calculated based on the average of the angle relative to the circumferential direction of 100 points of any groove portion observed in the photographed image.

[0196] (Surface roughness Rz)

[0197] The surface roughness Rz is the 10-point average roughness, which is the average value of the values ​​measured at any five locations according to JIS B0601 (1994). The surface roughness Rz of the entire surface layer is measured by observation using a laser microscope ("VK-9510" manufactured by KEYENCE). In the image taken at 400 times, the value calculated in the surface roughness mode in the analysis program (program name KEYENCEVKAnalyzer analysis application) is used as the surface roughness Rz of the entire surface layer. The surface roughness Rz of the surface layer in the area on the groove is measured by observation using a laser microscope (("VK-9510" manufactured by KEYENCE). In the captured image, the groove 0.01mm is selected in the surface roughness mode in the analysis program (program name KEYENCEVKAnalyzer analysis application). 2 The calculated value is taken as the surface roughness Rz of the groove portion.

[0198] (Adhesive thickness)

[0199] The measurement was performed by observing the radial cross section of the surface layer at 400 times magnification using a laser microscope ("VK-X100" manufactured by KEYENCE). Figure 4 As shown, the thickness of the binder polymer covering the roughness forming particles on the groove portion (binder thickness t1) and the thickness of the binder polymer covering the roughness forming particles on the flat portion (binder thickness t2) are measured. The measurements are performed at five locations at arbitrary positions, and the average values ​​are expressed.

[0200] (Image rating: Uneven)

[0201] The produced charging roller was mounted on a unit (black) of an actual machine ("IM C8000" manufactured by RICOH), and printing was performed at 25% halftone density under a 10°C × 10% RH environment, and evaluation was performed after 1 million sheets of durability. The image without unevenness was evaluated as good "0", and the image with unevenness was evaluated as bad "×".

[0202] (Image rating: horizontal stripes)

[0203] The produced charging roller was mounted on a unit (black) of an actual machine ("IM C8000" manufactured by RICOH), and printing was performed at a 25% density halftone under a 10°C × 10% RH environment, and the durability was evaluated after 1 million sheets. The image without horizontal streaks was evaluated as particularly good "0", and the image with horizontal streaks and a large impact on the image was evaluated as poor "×".

[0204] (Image evaluation: black spots (gray fog))

[0205] The produced charging roller was mounted on a unit (black) of an actual machine ("IM C8000" manufactured by RICOH), and printing was performed at 25% halftone density under a 10°C × 10% RH environment, and evaluation was performed after 1 million sheets of durability. The image was evaluated as good "○" if there was no black spot, and as bad "×" if even one spot was found.

[0206] (Image evaluation: vertical stripes)

[0207] The produced charging roller was mounted on a unit (black) of an actual machine ("IM C8000" manufactured by RICOH), and printing was performed at a 25% density halftone under a 10°C × 10% RH environment, and the durability was evaluated after 1 million sheets. The image without vertical streaks was evaluated as good "○", and the image with vertical streaks and a large impact on the image was evaluated as bad "×".

[0208] (Image evaluation: stripes along the concave and convex shapes)

[0209] The produced charging roller was mounted on a unit (black) of an actual machine ("IM C8000" manufactured by RICOH), and printing was performed at a 25% density halftone under a 10°C × 10% RH environment, and evaluation was performed after 1 million sheets of durability. The image was evaluated as good "○" if there were no streaks along the concave and convex shapes, and as bad "×" if streaks along the concave and convex shapes appeared in the image and had a great impact on the image.

[0210]

[0211]

[0212]

[0213]

[0214] The groove width of Comparative Example 1 is too small, and the roughness forming particles cannot enter the groove portion. Therefore, the difference between the surface roughness formed by the roughness forming particles on the plane portion and the surface roughness formed by the roughness forming particles on the groove portion is small, resulting in horizontal stripes caused by insufficient charging. In addition, if roughness forming particles of a size that can be accommodated in a small groove width are used, it is impossible to form a roughness that ensures sufficient discharge. In Comparative Example 2, the groove width is too large, and the difference in chargeability between the concave and convex parts of the surface of the charged roller is easily reflected in the image, resulting in vertical stripes. In addition, the groove width is too large, and the roughness forming particles cannot be evenly arranged in the groove portion. Therefore, unevenness after durability occurs. In addition, if roughness forming particles of a size that matches the large groove width are used, the convex parts formed by the roughness forming particles become too large, the surface roughness becomes too large, and the appropriate surface roughness cannot be formed. As a result, uniform discharge characteristics cannot be obtained. In addition, in Comparative Example 2, the groove width is too large, and the binder polymer of the roughness-forming particles covering the groove portion is easy to contact the photosensitive body. Therefore, not only the binder polymer of the roughness-forming particles covering the flat surface portion and the roughness-forming particles thereunder are worn, but also the binder polymer of the roughness-forming particles covering the groove portion and the roughness-forming particles thereunder are worn. During durability, the entire surface of the surface layer is worn, resulting in uneven image formation.

[0215] In Comparative Example 3, the groove depth is too small, and the difference between the surface roughness formed by the roughness forming particles on the plane portion and the surface roughness formed by the roughness forming particles on the groove portion is small, resulting in horizontal stripes caused by insufficient charging. In addition, if small roughness forming particles are used in combination with a small groove depth, it is impossible to form a roughness that ensures sufficient discharge. In Comparative Example 4, the groove depth is too large, and the difference between the surface roughness formed by the roughness forming particles on the plane portion and the surface roughness formed by the roughness forming particles on the groove portion becomes too large, the difference in charging becomes larger, and poor images (vertical stripes) occur. In addition, if large roughness forming particles are used in combination with a large groove depth, the difference between the surface roughness formed by the roughness forming particles on the plane portion and the surface roughness formed by the roughness forming particles on the groove portion becomes too large, and it becomes difficult to discharge.

[0216] In Comparative Examples 5 and 6, the width w2 of the flat portion deviates from the appropriate range (4 to 30 μm) of the groove width w1 of the groove portion. Therefore, the uniformity of the surface irregularities is reduced, resulting in uneven images after endurance.

[0217] In Comparative Examples 7 to 10, when the groove angle is within ±5° relative to the circumferential direction and the groove angle is relatively small, the ratio of the groove width of the groove portion to the width of the flat portion (w2 / w1) does not fall within the predetermined range, and the ratio of either the groove width of the groove portion or the width of the flat portion becomes too large. Therefore, the difference in chargeability between the groove portion and the flat portion is easily reflected in the image, resulting in vertical stripes.

[0218] In Comparative Examples 11 and 12, when the groove angle is greater than 5° and less than 22° relative to the circumferential direction, and the groove angle is slightly larger, the ratio of the groove width of the groove portion to the width of the plane portion (w2 / w1) does not fall within the predetermined range, and the ratio of either the groove width of the groove portion or the width of the plane portion becomes too large. Therefore, there is a charge difference between the groove portion and the plane portion, resulting in an uneven image after durability. In addition, in Comparative Example 12, when the formation angle of the groove portion is greater than ±5° relative to the circumferential direction, the width of the plane portion deviates to the smaller side compared to the groove portion. Therefore, the edge of the plane portion as the convex portion is easily worn by the circumferential rotation, and during durability, the difference in charge between the concave and convex portions caused by the wear of the convex portions becomes larger, resulting in a striped image along the concave and convex shapes.

[0219] In Comparative Examples 13 and 14, when the groove angle is greater than 22° and less than 46° relative to the circumferential direction, and the groove angle is relatively large, the ratio of the groove width of the groove portion to the width of the plane portion (w2 / w1) does not fall within the predetermined range, and the ratio of either the groove width of the groove portion or the width of the plane portion becomes too large. Therefore, there is a charge difference between the groove portion and the plane portion, resulting in an uneven image after durability. In addition, in Comparative Example 14, when the formation angle of the groove portion is greater than ±5° relative to the circumferential direction, the width of the plane portion deviates to the smaller side compared to the groove portion. Therefore, the edge of the plane portion as the convex portion is easily worn by the circumferential rotation, and during durability, the difference in charge between the concave and convex portions caused by the wear of the convex portions becomes larger, resulting in a striped image along the concave and convex shapes.

[0220] In Comparative Example 15, the groove angle exceeds 46° relative to the circumferential direction, which is too large. Therefore, the edge of the convex portion formed by the groove portion is easily worn by the circumferential rotation, and the difference in chargeability between the concave and convex due to the wear of the convex portion becomes larger during durability, resulting in a striped image along the concave and convex shape.

[0221] On the other hand, in the embodiment, one or more grooves extending in a direction within ±46° relative to the circumferential direction are regularly formed in the axial direction on the outer peripheral surface of the elastomer layer, and the groove width, groove depth and width of the plane portion of the groove portion are within a specific range. In addition, the angle θ of the extending direction of the groove portion relative to the circumferential direction and the ratio w2 / w1 of the groove width w1 and the width w2 of the plane portion of the groove portion are in a specific relationship, and the surface layer contains a binder polymer and roughness forming particles, and the roughness forming particles are respectively arranged on the plane portion and the groove portion of the elastomer layer. Therefore, it can be seen that the embodiment suppresses the problems of unevenness after durability, horizontal stripes, black spots (gray fog), vertical stripes, and stripes along concave and convex shapes in image evaluation, and the uniformity of discharge characteristics is excellent.

[0222] As mentioned above, although embodiment and Example of this invention were described, this invention is not limited at all to the said embodiment and Example, Various changes can be made in the range which does not deviate from the summary of this invention.

[0223] Description of Reference Numerals

[0224] 10: Charging roller;

[0225] 12: Axis;

[0226] 14: Elastomer layer;

[0227] 16: surface;

[0228] 18: particles for roughness formation;

[0229] 22: groove;

[0230] 24: plane part;

[0231] 16a: binder polymer;

[0232] 18a: Particles for forming roughness on the groove portion;

[0233] 18b: Particles for forming roughness on the plane portion;

[0234] 221: bottom surface of the groove;

[0235] w1: slot width;

[0236] w2: width of the plane part;

[0237] d: groove depth;

[0238] M: Area on the groove.

Claims

1. A charging roller for an electrophotographic device, comprising a shaft, an elastic layer formed on the outer peripheral surface of the shaft, and a surface layer formed on the outer peripheral surface of the elastic layer, wherein: One or more grooves extending in a direction within ±46° relative to the circumferential direction are regularly formed on the outer peripheral surface of the elastic layer in the axial direction. The groove width w1 of the groove portion is greater than or equal to 4 μm and less than or equal to 30 μm. The groove depth of the groove portion is not less than 2 μm and not more than 12 μm, The width w2 of the flat surface portion of the outer peripheral surface of the elastic layer, which is a portion other than the groove portion, is 4 μm or more and 30 μm or less. The relationship between the angle θ of the extending direction of the groove portion with respect to the circumferential direction and the ratio w2 / w1 of the groove width w1 of the groove portion and the width w2 of the planar portion is in the following relationship (A) to (C), The surface layer comprises a binder polymer and roughness-forming particles, The roughness forming particles are respectively arranged on the flat surface portion and the groove portion of the elastic layer. (A) -5°≤θ≤+5°, 0.7≤w2 / w1≤1.3 (B) When -22°≤θ<-5° or +5°<θ≤+22°, 1.0≤w2 / w1≤2.0 (C) When -46°≤θ<-22° or +22°<θ≤+46°, 1.2≤w2 / w1≤2.

6.

2. The charging roller for an electrophotographic apparatus according to claim 1, wherein The surface roughness Rz of the surface layer in the region on the groove portion is 2 μm or more and 16 μm or less, and the surface roughness Rz of the entire surface layer is 5 μm or more and 26 μm or less.

3. The charging roller for an electrophotographic apparatus according to claim 1 or 2, wherein: The roughness forming particles have an average particle size of 3 μm or more and 30 μm or less.

4. The charging roller for an electrophotographic apparatus according to any one of claims 1 to 3, wherein The material of the roughness forming particles is any one of polyurethane, polyamide and acrylic resin.

5. The charging roller for an electrophotographic apparatus according to any one of claims 1 to 4, wherein The thickness of the binder polymer covering the roughness-forming particles on the groove portion is greater than the thickness of the binder polymer covering the roughness-forming particles on the flat portion.

6. The charging roller for an electrophotographic apparatus according to any one of claims 1 to 5, wherein The difference between the thickness of the binder polymer covering the roughness-forming particles on the planar portion and the thickness of the binder polymer covering the roughness-forming particles on the groove portion is 4 μm or more and 16 μm or less.

7. The charging roller for an electrophotographic apparatus according to any one of claims 1 to 6, wherein The elastic layer includes at least one of isoprene rubber, nitrile rubber, and epichlorohydrin rubber.

8. The charging roller for an electrophotographic apparatus according to any one of claims 1 to 7, wherein The binder polymer of the surface layer is any one of polyurethane and polyamide.

9. The charging roller for an electrophotographic apparatus according to any one of claims 1 to 8, wherein The roughness forming particles are composed of one type of particles.

10. The charging roller for an electrophotographic apparatus according to any one of claims 1 to 9, wherein A mesh-like groove portion formed by intersecting groove portions extending in a direction within +46° with respect to the circumferential direction and groove portions extending in a direction within -46° with respect to the circumferential direction is formed on the outer peripheral surface of the elastic layer.

Citation Information

Patent Citations

  • Conductive roll

    WO2018025870A1